Atlantic impacts on subdecadal warming over the tropical Pacific in the 2000s - Mochizuki, Takashi; Watanabe, Masahiro (Frontiers in Climate, 2022)
A subdecadal (i.e., three-year running mean) variation over the tropical Pacific is very distinctively observed in the 2000s. Here, we have demonstrated that sea surface temperature (SST) anomalies in the tropical Atlantic contribute to forming high ocean-temperature anomalies in the tropical Pacific in the early 2000s by performing partial data assimilation of a global climate model. Low SSTs over the equatorial Atlantic change the Walker circulation, and the associated weakening of the Pacific trade winds raises the equatorial SST on subdecadal timescales. At the same time, a high SST anomaly is also generated in the off-equatorial North Pacific through deepening of the upper ocean thermocline due to an accompanying anticyclonic surface wind anomaly aloft. While the subtropical North Atlantic SSTs may help the subdecadal warming in the equatorial Pacific, the resultant SST anomalies show a one-year delay in the phase transition and are modestly accompanied by ocean thermocline deepening.